Current evidence-based therapy does not restore plasma apelin level in phenotypically diverse chronic heart failure patients - Wilson, Vinu; Prabhakar, Pankaj; Seth, Sandeep; Maulik, Subir K. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Apelin, endogenous peptide acting through its receptor (APJ), is the most potent inotropic agent known to man. Plasma apelin and cardiac APJ mRNA levels rise in early stages of chronic heart failure (CHF) but fall later in decompensated CHF. The effect of current evidence-based management of CHF on plasma apelin level is not known. We estimated change in plasma apelin level in CHF patients of diverse phenotypes treated with standard pharmacotherapy and compared it with the corresponding change in left ventricular ejection fraction (LVEF), plasma brain natriuretic peptide (BNP) level and quality of life (QoL). Methods: With ethical approval and written informed consent, venous blood samples were collected from 39 CHF [dilated cardiomyopathy (DCM) (n=21), restrictive cardiomyopathy (RCM) (n=9) and chronic constrictive pericarditis (CCP) (n=9)] patients and 10 age-matched healthy controls, at baseline and after 12 weeks. Plasma apelin and BNP were estimated by competitive ELISA (RayBiotech Inc.) and an auto-analyzer (Triage, Allere Inc.), respectively. QoL was assessed using Kansas City Cardiomyopathy Questionnaire (KCCQ). Nonparametric tests were applied and p-value <0.05 was considered significant. Results: Low LVEF, KCCQ score and high BNP levels were observed in all CHF patients compared to controls. Plasma apelin level was depressed in RCM and CCP patients compared to controls but not in DCM patients. These parameters did not change in any group after 3 months of standard pharmacotherapy. Conclusions: Current evidence-based management of CHF does not restore the depressed apelin-APJ axis. New drugs are required for specifically modulating this promising therapeutic target in CHF.